Colour Change of Hot Immersed Polymerized Acrylic Resin Steeped into Roselle Tea (Hibiscus sabdariffa) and Black Tea (Camellia sinensis) - Alfila Dinanti Nilasari; Dewi Kristiana; Achmad Gunadi; Surartono Dwiatmoko (Universitas Muhammadiyah Yogyakarta, 2022)
Steeping rosella tea and black tea are effective as denture cleaning agents as they contain flavonoids that can inhibit the growth of C. Albicans. Flavonoids in the brewing of rosella tea and black tea are found in pigment compounds, so when the acrylic resin is soaked in the steeping of roselle tea and black tea, it can cause discoloration.This study aims to compare the color changes of acrylic resin soaked in roselle tea and black tea with the same treatment. A total of 18 samples of acrylic resin were divided into three groups; six samples immersed in 20% concentrated roselle tea, six samples immersed in 20% concentration of black tea, and six samples immersed in steeping mineral water for 22 hours 30 minutes at room temperature. The research results' data were analyzed using the one-way Anova test. Acrylic resin soaked in steeping roselle and black tea experienced a color change, and the largest color change occurred in acrylic resin soaked in black tea. The results showed that hot polymerized acrylic resin soaked in black tea had a greater color change than that of acrylic resin soaked in roselle tea.